Race And Representation On Tv: The Influence Of Tv Status On Latino Identities - Gonzalez, Jesus (Departamento de Psicología y Comunicación de Texas A&M International University | Facultad de Trabajo Social y Desarrollo Humano de la Universidad Autónoma de Nuevo León, 2017)
It has been observed that most American TV media has taken on a format that seems to concern itself primarily with White, middle to high-income family situations. Even though the United States of America has a Latino population that reaches 17% (approximately 55 million Latinos—with Mexican Americans making up 63% of that number) and growing (Krogstad 2016), we still see a tremendous lack of Latino characters in American television. This leaves millions of Americans with no substantial representations that they can relate to, or form an identity off of. Instead, Latinos are forced into believing they are not important enough to merit TV roles and perhaps not really be American at all. This research was a content analysis of 79 scripted shows that aired through 2011-2015 to determine how often Latinos came out and how they were portrayed. Results showed that they appeared an average of six minutes on screen and they were generally depicted as criminals. Additionally, four focus group interviews were conducted,and participants also responded that shows tend to stereotype minorities while they showed White characters as authority figures. Both content analysis and focus group interviews found that Latinos lack strong representation in American television.